Pengaruh Kualitas Produk terhadap Keputusan Pembelian dan Kepuasan Konsumen dengan Peran Influencer sebagai Variabel Mediasi - Yulianti, Atik; Sutomo, Maskuri; Ponirin, Ponirin; Palawa, Muhammad Riswandi (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study used a quantitative method with the Nims Shop fashion store in Palu City as the object. The sample of 120 respondents was determined using a purposive sampling method using Roscoe's theory. Primary data was collected through a Google form questionnaire distributed through social media. Data analysis used partial least squares (PLS) to examine the relationship between product quality, the role of influencers, purchasing decisions, and consumer satisfaction. The results showed that product quality and the role of influencers significantly influence purchasing decisions and consumer satisfaction. Product quality not only plays a direct role in increasing satisfaction but also influences influencer perceptions, which impact purchasing decisions. Thus, an effective marketing strategy should consider both product quality and the role of influencers to increase consumer satisfaction.